Perancangan Implementasi VPN Server Menggunakan Protokol L2TP dan IPSec Sebagai Keamanan Jaringan - Prayogi Wicaksana; Febri Hadi; Aulia Fitrul Hadi (Universitas Putra Indonesia YPTK Padang, 2021)
One of the ways to maintain and improve the quality of service and security on the network of an agency of the Barangin Sub-District Office, Sawahlunto City (Central) is to add a VPN feature. Administrators who always monitor the flow of traffic by accessing routers and access points to find out network conditions. There are times when the Administrator is on a public network, he or she cannot access routers and access point devices because the Public IP obtained is Dynamic (random). To solve this problem, it is done through the Network Development Life Cycle (NDLC) method by combining the L2TP and IPsec VPN protocol systems on Mikrotik. A Virtual Private Network (VPN) is a private and secure network using a public network such as the internet. One of the bases for securing VPN technology is Internet Protocol Security (IPSec). IPSec is a protocol used to secure datagram transmission on TCP/IP-based networks. This study aims to design and implement a VPN network system by utilizing a public network, where this system provides advanced security enhancements on the internet network using IPSec. The information/data sent will be confidential with an automatic encryption method through the L2TP tunnel method from the server to the branch/client computer and vice versa. The VPN is implemented using a layer 2 (L2TP) tunneling protocol using two Mikrotik routers. There are few changes to the computer network configuration to minimize costs and implementation time. Tests are carried out to implement security on the network using the command prompt, where the admin observes packet loss and delay parameters to determine the increase in security quality on the network.